The mitochondrial transcription factor TFAM in neurodegeneration: emerging evidence and mechanisms - Kang, Inhae; Chu, Charleen T.; Kaufman, Brett A. (FEBS letters, 2018)
The mitochondrial transcription factor A, or TFAM, is a mitochondrial DNA (mtDNA)‐binding protein essential for genome maintenance. TFAM functions in determining the abundance of the mitochondrial genome by regulating packaging, stability, and replication. More recently, TFAM has been shown to play a central role in the mtDNA stress‐mediated inflammatory response. Emerging evidence indicates that decreased mtDNA copy number is associated with several aging‐related pathologies; however, little is known about the association of TFAM abundance and disease. In this Review, we evaluate the potential associations of altered TFAM levels or mtDNA copy number with neurodegeneration. We also describe potential mechanisms by which mtDNA replication, transcription initiation, and TFAM‐mediated endogenous danger signals may impact mitochondrial homeostasis in Alzheimer, Huntington, Parkinson, and other neurodegenerative diseases.